AN ASSESSMENT ON THE INFLUENCE OF MANAGEMENT COMMUNICATION PRACTICES ON STUDENTS’ UNREST IN PUBLIC SECONDARY SCHOOLS IN MERU COUNTY, KENYA - Marete, Jacob Bundi; Mugwe, Dr. Mary; Reche, Prof. George N. (IJRDO- Journal of Educational Research, 2017)
The purpose of this research was to investigate the school management practices oncommunication factors contributing to student unrest in public secondary schools in MeruCounty, Kenya. The objectives focused on critical challenges facing principals and teachers incommunicating effectively within the school. The research was carried out using the mixedmethod of research study in which the target population was 1,900 Principals, 1,900 Guidanceand Counselling Masters/Mistresses, 1,900 Discipline Masters, 1,900 student Presidents, 19,200students and 1 County Education Officer. The results showed that although the basiccommunication model of sender- message-receiver is straight forward, though communicationbarriers popularly referred to as “noise”. Noise in a school may be related to poor listening skills,poor language skills, a lack of trust and lack of follow-up/feedback on issues concerningstudents. Others include technical problems, poor selection of medium and misrepresentation ofthe message which may occur in the communication process.